2013
DOI: 10.1152/ajprenal.00233.2013
|View full text |Cite
|
Sign up to set email alerts
|

Renal anemia: from incurable to curable

Abstract: Renal anemia has been recognized as a characteristic complication of chronic kidney disease. Although many factors are involved in renal anemia, the predominant cause of renal anemia is a relative deficiency in erythropoietin (EPO) production. To date, exogenous recombinant human (rh)EPO has been widely used as a powerful drug for the treatment of patients with renal anemia. Despite its clinical effectiveness, a potential risk for increased mortality has been suggested in patients who receive rhEPO, in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 125 publications
0
36
0
2
Order By: Relevance
“…Erythropoiesis-stimulating agents (ESAs) are used worldwide to treat anemia due to CKD [2] . However, several large-scale trials reported that treatment with ESAs targeting higher hemoglobin targets has been associated with an increased risk of some major cardiovascular events [3][4][5][6] .…”
mentioning
confidence: 99%
“…Erythropoiesis-stimulating agents (ESAs) are used worldwide to treat anemia due to CKD [2] . However, several large-scale trials reported that treatment with ESAs targeting higher hemoglobin targets has been associated with an increased risk of some major cardiovascular events [3][4][5][6] .…”
mentioning
confidence: 99%
“…Indeed, it has been reported that in both CKD patients and animal models of CKD, the serum EPO levels are within the normal range or even increased . It is suggested that the serum EPO levels in CRF rats are, probably, insufficient to overcome renal anaemia . The remnant kidney of the CRF animals maintained some renal capacity to induce EPO synthesis, as showed by renal HIF‐2 α and EPO protein expression; even though, their expression levels were clearly reduced, when compared to the Sham kidneys, as the activation of HIF‐2 α appears to reduce with the progression of CKD .…”
Section: Discussionmentioning
confidence: 99%
“…Diyaliz öncesi kronik böbrek hastalarında dört haftada bir uygulanan CERA tedavisi anemiyi düzeltmiş ve Hb değerlerinin istenen sınırlar içinde kararlı kalmasını sağlamıştır [15,[43][44][45]. ESA tedavisi süresince Hb düzeyleri ayda bir kez, demir durumu tedavinin başlangıcında en az ayda bir kez daha sonra 3 ayda bir değerlendirilmelidir.…”
Section: Renal Aneminin Değerlendirilmesiunclassified
“…Kronik böbrek hastalarında ise aneminin derecesiyle plazma EPO düzeyleri arasındaki ilişki bozulmuştur. Kreatinin klirensi 40 ml/dak/1.73 m 2 altına düştüğünde ekskretuar böbrek fonksiyonu ile paralel olarak endokrin böbrek fonksiyonunun azalması EPO eksikliği ve anemi ile sonuçlanır [14,15]. Deneysel böbrek hasarı modellerinde EPO üreten hücrelerde fonksiyon bozukluğu ve myofibroblast transformasyonu olduğu gösterilmiştir [16].…”
unclassified